Weighted Estimates for Rough Maximal Functions with Applications to Angular Integrability. (16th July 2019) - Liu, Feng; Xu, Fangfang
Abstract : In this note we establish certain weighted estimates for a class of maximal functions with rough kernels along "polynomial curves" onR n . As applications, we obtain the bounds of the above operators on the mixed radial-angular spaces, on the vector-valued mixed radial-angular spaces, and on the vector-valued function spaces. Particularly, the above bounds are independent of the coefficients of the polynomials in the definition of the operators.